2013
DOI: 10.1111/ijfs.12374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laurel and myrtle extracts on the sensory, chemical and microbiological properties of vacuum‐packed and refrigerated European eel (Anguilla anguilla) fillets

Abstract: Summary The effects of extracted natural antioxidant (laurel and myrtle) on the sensory, chemical (TVB‐N, TBARS, PV, FFA and pH) and microbiological (total viable count, psychrotrophic bacteria and Enterbacteriaceae counts) properties of vacuum‐packaged European eel (Anguilla anguilla) stored at 4 ± 1 °C were investigated. The TBARS values of myrtle were significantly lower than that of other groups. The peroxide value was low for European eel treated with myrtle and laurel extract. The FFA‐free fatty acid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
(61 reference statements)
1
17
0
2
Order By: Relevance
“…The volume and percentage of plant extracts were decided based on literature information. (Gokoglu, Topuz, & Yerlikaya, 2009;Ozogul et al, 2014Ozogul et al, , 2017Ucak, Ozogul, & Durmus, 2011). Fish were drained and 100 g fish samples were placed on polyethylene packages with vegetable oil (sunflower) and vacuum packaged.…”
Section: Raw Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume and percentage of plant extracts were decided based on literature information. (Gokoglu, Topuz, & Yerlikaya, 2009;Ozogul et al, 2014Ozogul et al, , 2017Ucak, Ozogul, & Durmus, 2011). Fish were drained and 100 g fish samples were placed on polyethylene packages with vegetable oil (sunflower) and vacuum packaged.…”
Section: Raw Materialsmentioning
confidence: 99%
“…I. Ozogul et al (2014) investigated the effects of laurel and myrtle extracts on the sensory and quality aspects on the refrigerated eel. According to sensory results when the fish was not suitable for consumption sensory scores were 10.67 for control, 8.67 for laurel, 7.17 for myrtle.…”
Section: Sensory Analysismentioning
confidence: 99%
“…For sensory analysis, the quality index method scheme developed by some authors (Cardenas Bonilla et al 2007;Ozogul et al 2014) was used with modification ( Table 1). The scheme consisted of four quality parameters (flesh texture, flesh odour and colour, brightness).…”
Section: Test On Fish Filletsmentioning
confidence: 99%
“…For instance, consumption of red meat decreased the pleasantness′ of axillary odour . Unfortunately, the Japanese study does not tell us anything about the eating habits of the individuals tested; however, in this study, they found the ω7 monounsaturated acid, palmitoleic acid, which is a common constituent of fish oil , to be the origin of 2‐nonenal. This supports the assumption that a specific diet is the cause of the occurrence of culture‐specific odour compounds – also in old age.…”
Section: The Smell Of Old Agementioning
confidence: 63%